Prediction of Prostatic Involvement by Transitional Cell Carcinoma of the Bladder Using Pathologic Characteristics of the Bladder Tumor - Tabibi, Ali; Simforoosh, Nasser; Parvin, Mahmoud; Abadpour, Behrang; Abdi, Hamidreza; Khafri, Sorayya (Urology Journal, 2009)
Introduction: The aim of this prospective study is to determine the relationship between the pathologic characteristics of the transitional cell carcinoma (TCC) of the bladder and prostatic involvement. Materials and Methods: Sixty men with bladder TCC underwent standard radical cystoprostatectomy and were enrolled in this study. Vascular and perineural invasion, maximum diameter of the tumor, presence of carcinoma in situ, distance between the tumor and the bladder neck, and grade and local stage of the tumor were recorded and their relation with prostatic involvement was studied. In addition, hydronephrosis and age of the patients were included in the analysis. Results: The mean age of the patients was 63.9 Â± 11.1 years. Of 60 men included in this study, 15 patients were found to have prostatic involvement with TCC (25%). Univariate statistical analyses showed that vascular invasion and the distance between the tumor and the bladder neck were significantly related to the prostatic involvement (P = .007; P < .001). But, in the logistic regression, only the distance between the tumor and the bladder neck was significantly related to the prostatic involvement (P = .001). Conclusion: This study suggests that the probability of prostatic involvement in patients with bladder TCC tumors near the bladder neck is high. Prostate-sparing or capsule-sparing cystectomy should be avoided in such patients.